Pendampingan Pembelajaran Interaktif Menggunakan Teknik Jigsaw untuk Meningkatkan Keterampilan Membaca Siswa Kelas X di SMAN 4 Pamekasan - Dinar Vincy Yunitaka B; Fitrah Yuliawati; Jaftiyatur Rohaniyah (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2026)
An interactive mentoring program by using the Jigsaw technique was conducted to improve students’ reading skills through English reading texts. This program involved tenth-grade students at SMAN 4 Pamekasan. The activity was carried out in two sessions, each consisting of several stages, namely planning, action, observation, and reflection. The main objective of this program was to train students to improve their reading ability. The results of the interactive mentoring activity using the Jigsaw technique indicated that students initially felt unable to read English texts due to several factors, such as a lack of encouragement and motivation, limited vocabulary mastery, insufficient critical thinking skills, and difficulties in interpreting meanings appropriately based on English tense forms. However, most students found it easier to understand the content of reading texts through the Jigsaw technique, particularly in mastering reading skills using English.